Z > 4 low luminosity dusty galaxy candidates in the Frontier Fields A2744, AS1063 and A370. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Boone, Frédéric; Schaerer, Daniel; Richard, Johan; Clément, Benjamin; Egami, Eiichi; Rawle, Tim; Lutz, Dieter; Weiss, Axel; Staguhn, Johannes G.; ,
Abstract: We have conducted a LABOCA 870 μm follow-up of ten massive lensing clusters of the Herschel Lensing Survey (HLS, Egami et al. 2010) aiming at unveiling the yet hidden part of dusty star formation in the distant Universe. Among these clusters, A2744 and AS1063 are part of the Frontier Fields HST program. We also obtained 2 mm bolometer observations of A2744 and A370 with the GISMO array at the IRAM 30 m. We detected sources that are undetected with Herschel (PACS and SPIRE) implying either a very high redshift ( z > 4) or a very low dust temperature ( T <25 K). Their flux also imply a low intrinsic luminosity, L FIR < 10 12 L⊙ . Some of them are extended and could correspond to multiple sources or to multiple images of a lensed source. Substructures in the Sunyaev-Zeldovich effect could also contribute this very red submm emission. An ALMA program is ongoing to unveil the nature of these sources.